(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Need for Transcendence, Eternity and Freedom on Behalf to Assert Human Dignity and Religious Freedom In the context of the process of globalization and the phenomenon of secularization in the countries dominated by Western culture, it is seeing with necessity of new approaches of the relation between religious freedom and human dignity. History has revealed us that concern for the assertion of human dignity has also included concern for freedom of conscience, and the interest in respecting religious freedom has always brought increased concern for human dignity. This fact shows us that there is a correlative relationship between human dignity and religious freedom. Therefore, it is necessary to discover and enlarge the factors that can strengthen this relationship in order to achieve and develop a lasting social harmony that will be in the benefit of every citizen. In this article, we will refer to three fundamental needs of the human being that refer to human dignity and affirm the need for religious freedom: the need for transcendence (the transcendent immanent), the need for eternity (present eternity) and the need for freedom (freedom of deliberate self-limitation).